2016
DOI: 10.1177/0149206316628643
|View full text |Cite
|
Sign up to set email alerts
|

The Business Case for Women Leaders: Meta-Analysis, Research Critique, and Path Forward

Abstract: Since the 1990s, a growing body of research has sought to quantify the relationship between women's representation in leadership positions and organizational financial performance. Commonly known as the "business case" for women's leadership, the idea is that having more women leaders is good for business. Through meta-analysis (k = 78, n = 117,639 organizations) of the direct effects of women's representation in leadership (as CEOs, on top management teams, and on boards of directors) on financial performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
311
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(331 citation statements)
references
References 160 publications
12
311
1
7
Order By: Relevance
“…; Hoobler et al . ). Regardless, it is important that the criteria by which women's effectiveness as leaders are measured are useful and offer a fair picture of women's contributions.…”
Section: Gender Dandi From a Pwo Perspectivementioning
confidence: 97%
See 1 more Smart Citation
“…; Hoobler et al . ). Regardless, it is important that the criteria by which women's effectiveness as leaders are measured are useful and offer a fair picture of women's contributions.…”
Section: Gender Dandi From a Pwo Perspectivementioning
confidence: 97%
“…A meta‐analysis of 78 studies by Hoobler et al . () revealed that in cultures which promoted progressive attitudes toward gender parity, leadership by women was more likely to positively influence financial performance (e.g. sales performance).…”
Section: Gender Dandi From a Pwo Perspectivementioning
confidence: 99%
“…There are several studies regarding how women's leadership can affect company's financial performance [24,25]. The findings show that female-led firms were slightly better than their male-led counterparts in transmitting market performance into financial performance.…”
Section: Leadership Impact On Various Business Performances Is In Focmentioning
confidence: 99%
“…Unfortunately, the nature of essentializing itself, including what it means and how it happens, is rarely discussed in the literature on gender and leadership although it is a common theme in gender studies (Hoobler, Masterson, Nkomo, & Michel, ). Essentialism is the belief in an underlying, unchangeable essence that defines a person, category, or thing (Scholz, ).…”
Section: Gender Essentialismmentioning
confidence: 99%
“…Given that gender is most convincingly explained as a social construct, rather than an essentialist category, it is troubling that so much research on women and leadership continues to rely on essentialist categorizations of women to address the issues and challenges women face in the practice of leadership. In their meta‐analysis of research on the so‐called “business case for women leaders,” Hoobler et al, () critiqued precisely this nonnuanced view of gender as essentialist as one of the hindrances to research and theorizing on women's leadership. In the studies Hoobler et al identified, gender was equated to biological sex rather than “a system of relations, identity, and power” (p. 12), which influenced leadership behaviors of men and women.…”
Section: Leadership and Gender Essentialismmentioning
confidence: 99%